Star wars 5 : the empire strikes back - Kershner, Irvin (2000)
The battle for the galaxy intensifies in this thrilling fifth episode of the unfolding saga. As Imperial Forces launch an all-out attack on the Rebel Alliance, HAn Solo (HArrison Ford) and Princess Leia (Carrie Fisher) flee to Cloud City where they are captured by Darth Vader. Luke Skywalker (Mark Hamill) journeys to the mysterious, marshy planet of Dagobah, where the wise Jedi Master Yoda teaches the young hero the ways of the Force. Little does like Luke that all his Jedi training will be called upon so soon. A stunning revelation and a seeming life-or death duel with Darth Vader - await.